Mechanochemical models for generating biological pattern and form in development - Murray, J; Maini, P; Tranquillo, R (1988)
The central issue in development is the formation of spatial patterns of cells in the early embryo. The mechanisms which generate these patterns are unknown. Here we describe the new Oster-Murray mechanochemical approach to the problem, the elements of which are experimentally well documented. By way of illustration we derive one of the basic models from first principles and apply it to a variety of problems of current interest and research. We specifically discuss the formation of skin organ patterns, such as feather and scale germs, cartilage condensations in the developing vertebrate limb and finally wound healing.